Kaidah Fi Wadihi Dilalah Dalam Tafsir At Tabari - Fithrotin Fithrotin (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2022)
The methods used by Muslims in understanding divine revelation are very diverse. Various methods have been devised by humans in order to understand the Qur'an as a book of guidance from Allah, ranging from the classical to the contemporary. Among the books of interpretation produced by ancient scholars is Tafsir At Tabari, this interpretation is seen as one of the pioneers in the world of interpretation science and is seen as the first interpretation that interprets the Qur'an in its entirety from the Surah Al -Fatihah until the letter An-Nas which reached us with a bi al-ma'thur approach which was accompanied by analysis. Among the main points of study of scholars in Arabic literature is discussing the pronunciations that cover various aspects of it. In general, pronunciations can be seen from four aspects that both have special studies. First, the aspect of making pronunciation. Second, its use in meaning. Third, the designation of the pronunciation for a meaning involves its clarity and vagueness. And lastly, the way it is pointed to meaning. In fact, there are pronunciations or sentences that are easy to understand and some are difficult. Both are popular with the terms Wadih ad-Dalalah (obvious) and Khafi al-Dalalah (disguised). And each category consists of four sections.